Is prescription drug abuse in prisons changing? a preliminary study with prison doctors - Balcı Şengül, Ceyhan; Şengül, Cem; Albuz, Burcu (Journal of Dependence, 2015)
Objective: Since prescription drug abuse is a serious problem in prison settings, we set out to identify the most abused prescription drugs in prisons by asking primary care physicians employed there. Method: In our study, 15 physicians were interviewed face to face and 15 physicians were interviewed by e-mail. The survey included questions related to the city where the prison was located, number of inmates, estimated percentage of prescription drug abusers, and the top five prescription drugs most requested of the doctors. Results: The five most commonly listed drugs in response to the question regarding the doctors’ opinions as to which prescription drugs were the top five abused by prisoners were anti-epileptics gabapentin and pregabalin (80%), anti-influenza drugs containing dextromethorphan (66.6%), pain killers (non-steroidal anti-inflammatory drugs) and muscle relaxants containing phenprobamate (55%), quetiapine (46%), and the anticholinergic drug oxybutynin biperiden (40%). Discussion: The present study suggests that gabapentin, pregabalin, dextromethorphan, anti-inflammatory drugs, muscle relaxants, and quetiapine are the most abused prescription drugs among convicts. Prescription drug abuse is widely reported among convicts throughout the world. Conclusion: This study relies upon personal observation of prison physicians. Broader studies related to prescription drug abuse in prisons would lead us to a better understanding of the situation.